TÜRKİYE’DE CEZASIZLIK SORUNU VE ANAYASA MAHKEMESİ - (:unkn) unknown (My University, 2019)
Makalede cezasızlık sorununun anlamı, ulusal hukuktaki normatif dayanaklarıve Anayasa Mahkemesinin bu soruna olan katkısı ele alınmaktadır. Yöntem olarakkarşılaştırmalı metot kullanılmaktadır. Ulaşılan sonuç, Anayasa Mahkemesinin,İnsan Hakları Mahkemesinin konuyla ilgili yaklaşımını soyut olarak benimsediği;fakat temel ilkeleri somutlarken hataya düştüğü ve cezasızlık sorununu çözmek içinyeterince etkili olamayabildiğidir.

The article discusses the meaning and the normative bases of the concept of impunity in national law and questions whether there exists a contribution of the Turkish Constitutional Court (TCC) to the issue. The conclusion reached is that the TCC has failed to properly solve the problem of impunity and that the jurisprudence in the concrete cases of the TCC is incompatible with the case-law of the European Court of Human Rights, although those are consistent with each other with regards to principles.
IMPUNITY ISSUE IN TURKEY AND THE CONSTITUTIONAL COURT
Keywords: Uluslararası İlişkiler; Hukuk